Keputusan pemustaka dalam penelusuran informasi di Perpustakaan Balai Penelitian Tanaman Rempah dan Obat - Rushendi - Rushendi (Jurnal Kajian Informasi dan Perpustakaan, 2018)
The needs of library information need to be met to complete the information needs of the library users who generally have a variety of reasons to perform activities in accordance with their purpose. Information retrieval activity is one of the main activities of the library users at the library of the Research Institute for Spices and Medicinal Herbs (RISMH) to find the source of literature through the Online Public Access Catalog (OPAC) facility. The purpose of the research was to determine the decision of the user in searching for information. The study was conducted from November to December 2017, with materials obtained from the library literature search 2015 -2017 results form.  The study used the quantitative descriptive method, while the observed variables were: searching users; sources of the required information; subjects needed, and the relationship of the user with the library material searched. Data were analyzed descriptively. The result of the study showed the dominant user searching for information was the researcher; source of information required was documentation, and subject/commodity needed by the user which was medicinal plants. There is a correlation between the researcher’s decision and the searching of journal literature and documentation; student decisions by searching books, journals, and documentation; as well as the general/private user’s decisions with book search and documentation. The information retrieval service at the Balittro Library needs to be improved by linking the online search database with the Balittro website so it can increase the number of online collections.